РОЛЬ И ЗНАЧИМОСТЬ ГЕОБОТАНИЧЕСКИХ ОБСЛЕДОВАНИЙ (Experimental biology, 2011)
In given article value of geobotany in a science, geobotanical inspections and preparation of experts-geobotanists is considered
Keywords: geobotanical inspections; experts-geobotanists